Hypodontia phenotype in patients with epithelial ovarian cancer - Fekonja, Anita (Radiology and oncology (Ljubljana), 2015)
Background. Ovarian cancer is usually diagnosed in an advanced stage and the present clinical and diagnostic molecular markers for early OC screening are insufficient. The aim of this study was to identify potential relationship between the hypodontia and epithelial ovarian cancer (EOC). Patients and methods. A retrospective study was conducted on 120 patients with EOC treated at the Department of Gynaecologic and Breast Oncology at the University Clinical Centre and 120 gynaecological healthy women (control group) of the same mean age. Women in both groups were reviewed for the presence of hypodontia and the patients with EOC also for clinicopathological characteristics of EOC according to hypodontia phenotype. Results. Hypodontia was diagnosed in 23 (19.2%) of patients with EOC and 8 (6.7%) controls (p = 0.004; odds ratio OR = 3.32; confidence interval CI, 1.42-7.76). There was no statistically significant difference in patients with EOC with or without hypodontia regarding histological subtype (p = 0.220); they differed in regard to FIGO stage (p = 0.014; OR =3.26; CI, 1.23%8.64) and tumour differentiation grade (p = 0.042; OR = 3.1; CI, 1.01-9.53). Also, bilateral occurrence of EOC was more common than unilateral occurrence in women with hypodontia (p = 0.021; OR = 2.9; CI, 1.15-7.36). We also found statistically significant difference between the ovarian cancer group and control group in presence of other malignant tumours in subjects (p < 0.001). Conclusions. The results of the study suggest a statistical association between EOC and hypodontia phenotype. Hypodontia might serve as a risk factor for EOC detection.
Keywords: dejavniki tveganja; hipodontija; jajčniki; rak (medicina); zgodnja diagnostika